Composition and biomass of phytoplankton assemblages in coastal Antarctic waters: A comparison of chemotaxonomic and microscopic analyses - Garibotti, Irene A. (2003)
We describe the distribution of phytoplanktonic community composition and biomass from the Western Antarctic Peninsula coast (between 64° and 68° S) using 2 analytical techniques: microscopy and HPLC of photosynthetic pigments. Phytoplankton biomass was estimated as chlorophyll a (chl a) by HPLC and chemotaxonomic quantification of microalgae biomass was performed by multiple regression analysis of pigment concentrations. For the estimation of chl a: diagnostic pigment ratios, it was found of primary importance to differentiate between phytoplankton assemblages within the study area. Three assemblages were differentiated according to their total standing stock and analyzed independently. Phytoplankton biomass was also estimated as carbon (C) concentration by microscopic analysis of cell abundance and biovolumes. Microscopy and chemotaxonomy give a high level of agreement for phytoplankton characterization, showing an on/offshore gradient, with high diatom and cryptophyte biomass in coastal waters, and a mixed assemblage with low biomass in open waters. This gradient was not observed in total cell abundance, indicating that the biomass gradient is controlled by cell size. Microscopy also showed shifts in diatom species throughout the area. C and chl a biomass estimates for the individual microalgae groups were strongly correlated for cryptophytes, chlorophytes and most diatoms, but did poorly for dinoflagellates, prymnesiophytes and chrysophytes. From this study, we conclude that both microscopy and chemotaxonomy can be used to accurately characterize phytoplankton assemblages, but some limitations are present in both techniques. Based on phytoplankton C concentrations, we estimated an average in situ growth rate of 0.28 d-1. In situ cell C:chl a ratios had high variability (from 40 to 220) and were non-linearly related to sample growth rates. Significant differences were found among average C:chl a ratios of low (<1 μg chl a 1-1) and high biomass communities (>1 μg chl a l-1), with values of 112 and 74 μg C μg-1 chl a, respectively. In addition, our results support the hypothesis that C quotas of diatoms and other microalgae do not differ greatly from each other, as previously believed.